Jobs or Privileges : Unleashing the Employment Potential of the Middle East and North Africa - Schiffbauer, Marc; Sy, Abdoulaye; Hussain, Sahar; Sahnoun, Hania; Keefer, Philip (Washington, DC: World Bank, 2014)
This report shows that in MENA, policies that lower competition and create an unleveled playing field abound and constrain private sector job creation. These policies take different forms across countries and sectors but share several common features: they limit free-entry in the domestic market, exclude certain firms from government programs, increase regulatory burden and uncertainty on non-privileged firms, insulate certain firms and sectors from foreign competition, and create incentives that discourage domestic firms from competing in international markets. The report shows that such policies are often captured by a few privileged firms with deep political connections, and that these policies persist despite their apparent cost to society. The millions of workers, consumers, and the majority of entrepreneurs who bear the brunt of that cost are often unaware of the adverse impact of these policies on the jobs and economic opportunities to which they aspire. This limits the scope for internal country debate and curtails the policy dialogue necessary for reform. Thus, Middle East and North Africa (MENA) countries face a critical choice in their quest for higher private sector growth and more jobs: promote competition, equal opportunities for all entrepreneurs and dismantle existing privileges to specific firms or risk perpetuating the current equilibrium of low job creation.